ہندومت اور اسلام کے جنگی قوانین و ضوابط کا تقابلی جائزہ: A comparative study of the laws and regulations of warfare in Hinduism and Islam - Sana Tabussum; Dr. Farhat Naseem Alvi (jihat-ul-islam, 2025)
War, though an unfortunate reality of human history, has always been governed by ethical frameworks and religious principles in many civilizations. This research aims to present a comparative study of the laws and regulations of war in Hinduism and Islam, highlighting the philosophical underpinnings, moral restrictions, and strategic guidelines prescribed by both religions. While both traditions differ in theology and metaphysics, they offer surprisingly structured and morally conscious approaches to warfare. In Hinduism, texts such as the Mahabharata, Manusmriti, and Bhagavad Gita outline the concept of Dharma Yuddha (righteous war), which emphasizes ethical conduct, protection of the innocent, and spiritual merit for just warriors. On the other hand, Islam, through the Qur’an, Hadith, and the historical example of the Prophet Muhammad (peace be upon him), advocates for Jihad as a struggle against injustice, governed by strict ethical codes, including prohibition of harming non-combatants, property, or the environment. This study draws upon classical religious texts, commentaries, and scholarly interpretations to explore how both religions conceptualize war not as a means of conquest but as a last resort in the pursuit of justice and peace. By understanding these principles, we gain insight into the human quest for moral conduct even in times of conflict , a reminder that even in war, humanity must not be abandoned.